Investigating The Influence Of Group Work On Creativity, Motivation And Writing Achievement : The Case Of Second Year Students At The Department Of Letters And English, University Frères Mentouri, Constantine 1 - Elmechta, Lamia (المجلة الجزائرية للأمن الإنساني, 2021)
One of the major targets of the reform that the Algerian educational system, notably higher education, has witnessed during the last decade is to achieve autonomy in learning. This latter can be well attained by the policy of collaborative, cooperative or, in simple words, group work. Regarding foreign language learning, group work has, recently, gained a wide popularity. In this context, the present work aims at investigating the effects of group work on creativity, motivation, and EFL writing achievement. Group work was hypothesized to enhance second year students’ creativity and motivation, and was predicted to improve their writing achievement. In testing this hypothesis, an observational study was applied to a sample of seventy students studying at the department of Letters and English, University Frères Mentouri, Constantine 1, and a questionnaire was administered. Concerning the results of the observation, group work results were found more significant, basically in producing creative content, in increasing the students’ motivation, as well as in making less grammar and punctuation mistakes. Regarding the results of the questionnaire, most of the respondents (nearly 90%) were proved to support the idea of group work in learning and creativity, in increasing motivation, as well as in improving writing achievement.